Puerarin Suppress Apoptosis of Human Osteoblasts via ERK Signaling Pathway - Ling-juan Liu; Li-qun Liu; Tao Bo; Shi-jun Li; Zhen Zhu; Rong-rong Cui; Ding-an Mao (International Journal of Endocrinology)
Puerarin, the main isoflavone glycoside extracted from Radix Puerariae, is an isoflavone traditional Chinese herb. Previous studies have demonstrated that puerarin could regulate osteoblast proliferation and differentiation to promote bone formation. However, the effect of puerarin on the process of human osteoblasts (hOBs) apoptosis is still unclear. In this study, we detected the function of puerarin on serum-free-induced cell apoptosis using ELISA and TUNEL arrays and then found that the mortality of hOBs was significantly decreased after exposure to 10−10–10−6 M puerarin and reached the maximal antiapoptotic effect at the concentration of 10−8 M. In addition, compared with the control group, puerarin notably increased the Bcl-2 protein levels while it decreased the Bax protein levels in the hOBs in a dose-dependent way. 10−7 M puerarin decreased the Bax/Bcl-2 ratio with a maximal decrease to 0.08. Moreover, puerarin activated ERK signaling pathways in hOBs, and the antiapoptotic effect induced by puerarin was abolished by incubation of ERK inhibitor PD98059. Similarly, the estrogen receptor antagonist ICI182780 also suppressed the inhibitory effect of puerarin on hOBs apoptosis. In conclusion, puerarin could prevent hOBs apoptosis via ERK signaling pathway, which might be effective in providing protection against bone loss and bone remolding associated with osteoporosis.